2015
DOI: 10.3390/molecules20047097
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Marine Natural Compounds and Their Derivatives with Anti-Cancer Activity Reported in 2012

Abstract: Although considerable effort and progress has been made in the search for new anticancer drugs and treatments in the last several decades, cancer remains a major public health problem and one of the major causes of death worldwide. Many sources, including plants, animals, and minerals, are of interest in cancer research because of the possibility of identifying novel molecular therapeutics. Moreover, structure-activity-relationship (SAR) investigations have become a common way to develop naturally derived or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 83 publications
(127 reference statements)
0
36
0
Order By: Relevance
“…Marine environments are unlike terrestrial environments, and the abundant biodiversity of marine organisms produce novel and bioactive natural products. In the past decade, more than 3000 newly identified marine-derived compounds have been reported having novel therapeutic uses [ 27 ]. Peach et al found that auromomycin inhibits biofilm formation by Vibrio cholerae with an IC 50 of 60.1 μM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine environments are unlike terrestrial environments, and the abundant biodiversity of marine organisms produce novel and bioactive natural products. In the past decade, more than 3000 newly identified marine-derived compounds have been reported having novel therapeutic uses [ 27 ]. Peach et al found that auromomycin inhibits biofilm formation by Vibrio cholerae with an IC 50 of 60.1 μM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marine natural products have demonstrated pharmaceutical potential, particularly for the development of anticancer [ 27 ], antiviral [ 28 ] and antibacterial drugs [ 29 ]. The soft corals of the Sinularia genus are well known for producing bioactive and structurally versatile natural compounds [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Used empirically in traditional medicine for thousands of years without fully knowing their mechanisms of action, natural products from marine or terrestrial organisms feature a wide variability of chemical structures that modulate a wide range of biological effects (Cerella et al 2014;Morceau et al 2015;Schnekenburger et al 2014Schnekenburger et al , 2015Schumacher et al 2011). These compounds act on a number of therapeutic targets, including processes involved in cancer development and progression (Gaascht et al 2010;Lee et al 2015;Muller et al 2015;Sawadogo et al 2012Sawadogo et al , 2015Teiten et al 2013). Among the vast natural chemical library, we can note isolated plant substances, such as curcumin (Teiten et al 2010(Teiten et al , 2011, aurones (Zwergel et al 2012), plumbagin (Gaascht et al 2014) and fungal secondary metabolites embellicines (Ebrahim et al 2013), which were recently investigated for their chemopreventive and anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 11 was furnished via treatment of the 2,3-dichloroquinoxaline derivative 1 with two moles of sodium azide in ethanol as shown in Scheme 3. Compound 11 was found to be in tautomeric equilibrium with the 2,3-diazido derivative 11 1 . Its IR spectrum revealed the absence of the characteristic HNNH 2 group band and its mass spectrum showed a molecular ion peak at m/z 290 (M + ; 7%).…”
Section: Chemistrymentioning
confidence: 99%
“…According to the World Health Organization (WHO), the incidence of this disease is about 6 million cases per year [1][2][3]. Cancer cannot be defined as a single disease, but rather a collection of diseases [4].…”
Section: Introductionmentioning
confidence: 99%